Atmospheric Pressure Plasma Jet as an Accelerator of Tooth Bleaching - Vedran Šantak; Rok Zaplotnik; Slobodan Milošević; Eva Klarić; Zrinka Tarle (University of Zagreb. School of Dental Medicine, 2014)
Objective: To study the effect of atmospheric pressure plasma (APP) jet as a potential accelerator of the degradation of hydrogen peroxide in bleaching gels which could lead to better and faster bleaching. Material and Methods: 25 pastilles of hydroxylapatite were colored in green tea for 8 hours and were randomly divided into five groups (n = 5). The bleaching process was performed with 30% and 40% hydrogen peroxide (HP) gel alone and in conjunction with helium APP jet. During the bleaching treatment, optical emission spectroscopy and non-contact surface temperature measurement using pyrometer were performed. Color of the pastilles was determined by a red- green-blue (RGB) colorimeter. PH values of bleaching gels were measured before and after the plasma treatment on additional 10 pastilles using a pH meter with contact pH electrode. Results: The color measurements of pastilles before and after the treatment showed that treatment with APP jet improved the bleaching effect by 32% and 15% in the case of 30 % and 40% HP gel. Better results were obtained approximately six times faster than with a procedure suggested by the bleaching gel manufacturer. Optical emission spectroscopy proved that plasma has a chemically active role on the gel. After the APP treatment, pH values of bleaching gels dropped to about 50-75% of their initial value while the surface temperature increased by 8-10˚C above baseline. Conclusion: The use of plasma jet provides more effective bleaching results in a shorter period of time without a significant temperature increase which may cause damage of the surrounding tissue.